A DESCRIPTIVE STUDY TO ASSESS THE KNOWLEDGE ON BREAST CANCER AND UTILIZATION OF MAMMOGRAM AMONG WOMEN IN SELECTED VILLAGES OF UDUPI DISTRICT, KARNATAKA - Shadap, Arkierupaia; Pais, Maria; Prabhu, Anusuya (Journal of Health and Allied Sciences NU, 2014)
Breast cancer was considered to be one amongst the most commonly cancer disease in the world. Now it is considered to be the second cancer disease among women in India, with most of the affected population is in the urban areas. Breast cancer is seen mostly after the age of 40 years. According to the Cancer fact 2012, breast cancer is now seen to be among women aged from 35 years above.Materials and methods: The study was a descriptive survey study to assess the knowledge on breast cancer, awareness and utilization of mammogram among 320 married and unmarried women who were willing to participate in the study. After the consent, a questionnaire prepared by the investigator was given to them.Results: Majority 46.6% had low knowledge for breast cancer. There was an association between knowledge and age, marital status, education and source of information about breast cancer and it was found to be significant (p< Mammogram is underutilized among participants, from the total number of population i.e; n = 320, only 19.1% (61) were aware of mammogram. Out of 19.1% (61) who were aware of mammogram, did not utilise it.Conclusion: The study concluded that women have low knowledge on breast cancer and very less population was aware of mammogram which is one of the screening tests for breast cancer. Their low knowledge on breast cancer and unaware of the screening test is the main reason for not utilising mammogram even those who are aware of it. So, nurses as health care members play an important role in providing information and educating the community people.
Keywords: Knowledge; breast cancer; utilization; mammogram